Large-scale drug screens support precision medicine - Gray, Joe W. (Cancer Discov, 2015)
The major challenge underlying the emerging precision medicine initiative is to make links between cancer subsets and drugs that can be used to guide treatment of individual patients leading to improved outcomes and decreased toxicity. Schreiber et al [1] support this effort by reporting measurements of responses of 664 adherent cancer cell lines to 70 FDA approved drugs, 100 experimental compounds and 311 small molecule probes. They use a using a novel ACME algorithm to identify drug mechanisms of action, molecular markers of response, responsive cancer subtypes and compounds that produce synergistic cell inhibition.